THE INFLUENCE OF SALES PROMOTION AND BRAND IMAGE ON BUYING DECISIONS IN THE MARKETPLACE SHOPEE - Nugroho, Jati (Universitas YPPI Rembang, 2022)
This study aims to explain the effect of Sales Promotion and Brand Image on buying decisions in the Shopee marketplace, a case study of shopee users in Semarang. The population in this study were 100 shopee users who live in Semarang. This study used multiple regression analysis with the help of SPSS 25 software. Based on calculations using regression tests, the results showed the regression equation Y = 6.783 + 0.213X1 + 0.322X2. The calculated F value is 12.637 which is greater than F table 3.09. Likewise with the t test, t count is greater than t table, and has a significance less than the 0.05 level of significance. So it can be concluded that there is an influence between Sales Promotion (X1) and Brand Image (X2) variables on Buying Decisions (Y) for Shopee users in Semarang. Based on calculations using SPSS shows that the coefficient of determination of 57.7% of the purchasing decision variables is influenced by Sales Promotion and Brand Image while the remaining 42.3% is influenced by other variables.Keywords: Sales Promotion; Brand Image; Buying Decision.